Lip repositioning for the treatment of excess gingival display: A systematic review. Issue 2 (27th November 2017) - Tawfik, Omnia K; El‐Nahass, Hani E.; Shipman, Peter; Looney, Stephen W.; Cutler, Christopher W.; Brunner, Mark
Abstract: Background: Lip repositioning is a conservative surgical technique used to treat excess gingival display. An array of modifications has been introduced to the technique over time and as studies show the technique and its modifications to be successful, there is little standardized information for clinicians to make informed decisions when choosing this technique for the treatment of patients with excessive gingival display (EGD). Objectives: To review the current literature on the topic of lip repositioning for the treatment of excessive EGD, exploring outcome, and result longevity. Methods: A structured systematic search was carried out using the Ovid database and Web of Science to identify published studies on lip repositioning technique. Search was restricted to studies in the English language, describing a surgical intervention. Case reports were included as the number of published studies was limited. Results: The electronic search identified 93 articles, hand search identified 1 article, and reference search identified 1 article. After excluding duplicates and screening articles, a total of 22 articles met the inclusion criteria. An estimated mean improvement of 3.4 mm (95% confidence interval, 3.0‐3.8 mm) was found possible with lip repositioning. Data analysis was performed using only 4 studies, amounting to a total of 33 patients. Potential risk of bias was identified in some of the studies included. Conclusions: Despite the limited available studies on lip repositioning, an estimated mean improvement of 3.4 mm was found to be possible with surgical lip repositioning, suggesting that the technique could be used successfully to treat EGD. However, more studies are necessary to properly evaluate the treatment approach and stability of the technique. Clinical significance: Recently, the demand for esthetics has significantly increased, driven by increased patient awareness and the search for an ideal smile. Creating the perfect smile is an intricate process that requires a multidisciplinary approach, with careful consideration of the lips and the gingival outline. Excess gingival display results in an unaesthetic smile, lip repositioning offers a comparatively simple solution for this problem. While the quality literature on this topic is limited statistical analysis of collected studies show that an estimated mean improvement of 3.4 mm can be achieved with surgical lip repositioning.